Stand inventory data from the 10‐ha forest research plot in Uholka: 15 yr of primeval beech forest development - Jonas Stillhard; Martina Hobi; Lisa Hülsmann; Peter Brang; Christian Ginzler; Myroslav Kabal; Jens Nitzsche; Gilbert Projer; Yuriy Shparyk; Brigitte Commarmot (Ecology, 2019)
Forests dominated by European beech ( Fagus sylvatica L.) are among both the most widespread in Europe and the most intensely exploited globally. One of the largest remnants of unmanaged beech forests in Europe is the Uholka‐Shyrokyi Luh forest in Transcarpathia, Ukraine, covering 8,800 ha of primeval forest. In 2000, a permanent forest plot of 10 ha has been established in the Uholka massif. All living and dead trees with a diameter at breast height ( DBH ) ≥ 60 mm were identified to species, DBH measured, stems tagged and mapped. Since then, the plot has been remeasured in 2005, 2010, and 2015. In total, 4,820 individual trees were measured with 14,116 individual measurements throughout all four inventories. In spring 2018, an Airborne Laser Scan was carried out, covering the Uholka‐Shyrokyi Luh forest. This data set allows us to derive a high‐resolution digital elevation model ( DEM ) of the plot area. European beech covers a share of ≈ 95% of the basal area ( BA ) of all living stems. While BA was relatively stable throughout all inventories (≈ 38 m 2 /ha), the number of stems increased considerably between 2010 and 2015 from 290 to 430 stems/ha. Additionally, the proportion of beech stems decreased from 95% in 2010 to 86% in 2015. The continuity of the share of beech on BA and the decrease in number of stems can be traced back to disturbance events, which led to an increase of more light demanding species in the recruitment but did not alter the distribution of BA as these small trees contribute very little to BA . The data set allows for important insights into the development and the spatial and temporal dynamics of primeval beech forests. It can be used to quantify the demographic processes growth, mortality, and recruitment, and to study inter‐ and intraspecific effects on demographic rates, stand structure, and species composition. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.